The Gastrointestinal Helminth Heligmosomoides bakeri Suppresses Inflammation in a Model of Contact Hypersensitivity - Filbey, Kara J.; Mehta, Palak H.; Meijlink, Kimberley J.; Pellefigues, Christophe; Schmidt, Alfonso J.; Le Gros, Graham (Frontiers in Immunology, 2020)
Helminths regulate host immune responses to ensure their own long-term survival. Numerous studies have demonstrated that these helminth-induced regulatory mechanisms can also limit host inflammatory responses in several disease models. We used the Heligmosomoides bakeri (Hb) infection model (also known as H. polygyrus or H. polygyrus bakeri in the literature) to test whether such immune regulation affects skin inflammatory responses induced by the model contact sensitiser dibutyl phthalate fluorescein isothiocynate (DBP-FITC). Skin lysates from DBP-FITC-sensitised, Hb-infected mice produced less neutrophil specific chemokines and had significantly reduced levels of skin thickening and cellular inflammatory responses in tissue and draining lymph nodes (LNs) compared to uninfected mice. Hb-induced suppression did not appear to be mediated by regulatory T cells, nor was it due to impaired dendritic cell (DC) activity. Mice cleared of infection remained unresponsive to DBP-FITC sensitisation indicating that suppression was not via the secretion of Hb-derived short-lived regulatory molecules, although long-term effects on cells cannot be ruled out. Importantly, similar helminth-induced suppression of inflammation was also seen in the draining LN after intradermal injection of the ubiquitous allergen house dust mite (HDM). These findings demonstrate that Hb infection attenuates skin inflammatory responses by suppressing chemokine production and recruitment of innate cells. These findings further contribute to the growing body of evidence that helminth infection can modulate inflammatory and allergic responses via a number of mechanisms with potential to be exploited in therapeutic and preventative strategies in the future.